Platelet Factor 3 and the Generalized Shwartzman Reaction - Müller-Berghaus, G; Goldfinger, D; Margaretten, W; McKay, D. G (Thrombosis and Haemostasis, 1967)
The mechanism of “provocation” of the generalized Shwartzman reaction was studied in rats and rabbits. Rats were “prepared” for the reaction by epsilon-aminocaproic acid or pregnancy, rabbits by Thorotrast or endotoxin. Infusions of different preparations of platelet factor 3 activity were not capable of “provoking” the Shwartzman reaction. Purified bovine platelet factor 3, rabbit brain tissue extracts in the form of “so-called” partial thromboplastin or a soya bean phospholipid preparation were used. The results suggest that in addition to the aggregation of platelets and the release of platelet factor 3 other actions of endotoxin are essential to the production of the generalized Shwartzman reaction.